2018
DOI: 10.1016/j.ecoser.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of economic benefits for public investment in MPAs

Abstract: MPAs enhance some of the Ecosystem Services (ES) provided by coral reefs and clear, robust valuations of these impacts may help to improve stakeholder support and better inform decision-makers. Pursuant to this goal, Cost-Benefit Analyses (CBA) of MPAs in 2 different contexts were analysed: a community based MPA with low tourism pressure in Vanuatu, and a government managed MPA with relatively high tourism pressure, in Saint Martin. Assessments were made on six ES: fish biomass, scenic beauty, protection again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…While social scientists are increasingly called on to assess human well-being outcomes of MPAs 28 , MPA development and management continues to be primarily occurring without consistent quantitative or qualitative monitoring of well-being outcomes 29,30 . We need to move towards ensuring the long-term well-being of people and communities that depend on marine The process of creating MPAs, that are small, local, and managed by communities, has numerous benefits for human empowerment and well-being, notwithstanding environmental outcomes [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…While social scientists are increasingly called on to assess human well-being outcomes of MPAs 28 , MPA development and management continues to be primarily occurring without consistent quantitative or qualitative monitoring of well-being outcomes 29,30 . We need to move towards ensuring the long-term well-being of people and communities that depend on marine The process of creating MPAs, that are small, local, and managed by communities, has numerous benefits for human empowerment and well-being, notwithstanding environmental outcomes [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…The economic benefits of expanding MPA coverage are the maintained or enhanced flows of ecosystem services that are provided by protected marine ecosystems [6,45,46]. The marine ecosystems included in our assessment are coral reefs, coastal wetlands and mangroves.…”
Section: Benefit Estimationmentioning
confidence: 99%
“…We cataloged and present here (Tables 2A,B, 3) each piece of literature based on scope, environment considered (marine or terrestrial), the costs reported, type of data, and eligibility for inclusion in our quantitative comparison. Papers and articles include projections for real cases, estimations for hypothetical scenarios, and observations from ongoing efforts Some studies are site-or region-specific, in which case their geographic focus is also referenced (Green et al, 2012;Rojas-Nazar et al, 2015;Pascal et al, 2018). Other studies have used a collection of case examples or data sets to construct cost models to both identify variables that influence costs, as well as to project costs of…”
Section: Literature Reviewmentioning
confidence: 99%